MEMBEBASKAN POSITIVISME HUKUM KE RANAH HUKUM PROGRESIF (Studi Pembacaan Teks Hukum Bagi Penegak Hukum) - ASukris Sarmadi (Faculty of Law, Universitas Jenderal Soedirman, 2012)
According to the law of UU No. 48 Year 2009 about Judicial Power Section 5 sentence (1) which is on its say; core express that judge is obliged to dig of law, following, and comprehending values law and sense of justice which live in society. Hence law shall comprehend to place forward sense of justice which live in society. Law have the target of its social, advocating and protecting society citizen. If text in law at variance with target of social hence text in law that have to be transferred in essence norm that at target of its social in the form of society sense of justice, defence and protection to society citizen. This matter to free positive law of inequitable of law so that law remain to in progressive target. Key words: Justice, norm, positive law, progressive law, legislation.